The Impact of Governance Practices on the Operating Performance: A Study on the Indonesian State-Owned Enterprises - Warganegara, Dezie L.; Alamsjah, Firdaus; Soentoro, Melisa (International Research Journal of Business Studies, 2012)
This study aims to investigate the corporate governance practices on State-Owned Enterprises (SOEs) and to find out their impacts on the operating performance of the firms. This study finds out the substantial improvements of the quality of corporate governance practices in public-listed Indonesian SOEs. Total corporate governance (CG) compliance score and each component score show an upward trend improvement. With regard to the relationship between CG compliance and operating performance, as represented by Return on Assets, Net Profit Margin, and Assets Turnover, this study finds out that there is a direct relationship between the governance quality and operating performance. This positive relationship is cpused by the reduction of the operating cost and not coused by the increase of sales or the better use of assets.